PERSEPSI IBU TENTANG OBESITAS PADA ANAK USIA 1-3 TAHUN DI POSYANDU DUSUN BATAN KRAJAN DESA BATAN KRAJAN KECAMATAN GEDEG KABUPATEN MOJOKERTO - Ratnaningsih, Tri; Widyaningrum, Nina (JURNAL KEPERAWATAN BINA SEHAT, 2012)
The over nutriens we always call with obesity. Therefore researcher want to know how mother’s opinion for nutrition and also the condition of children who get obesity. The purpose research is to know mother’s perception at posyandu Batan Krajan orchard, Batan Krajan village, Gedeg district, Mojokerto regency about obesity in children aged 1-3 years.This research used description research design. The population are mother’s at Batan Krajan orchard, Batan Krajan village who have child in 1-3 years. There are 32 sample mother, tehnic of sampling is Nonprobability Sampling with consecutive sampling method. The variable in this research is mother’s perception about obesity in children aged 1-3 years. The data to get with given the questioner. Manufacturing data doing by enter on the distribution table and with used the formula T skor with interpretation is positive perception if T skor > mean T, and negative perception if T skor ≤ mean T. The result of the research it’s saw that from 32 respondent are 17 resondent (53 percent) have positive perception and 15 respondent (47 percent) have negative perception. So more than a half respondent have positive perception.This is because there are positive awareness,opinion, and experience in ther self that change negative perception be positive perception about obesity. Therefore the mothers who had a negative perception cause by less information. So the role of healt workers as information givened is survived and to improve, because that information most of came from healt workers.Key word : mother’s perception, obesity, and children in 1-3 years